Inherent propensity of amnion-derived mesenchymal stem cells towards endothelial lineage: Vascularization from an avascular tissue - Warrier, Sudha; Haridas, N.; Bhonde, R. (2012)
One of the most pressing problems in injury is wound healing and blood vessel formation. The amniotic membrane is important in clinical applications as it is pro-angiogenic, anti-fibrotic and anti-scarring and has low immunogenicity. In this study, we characterized amniotic membrane mesenchymal stem cells (AMMSCs) by their trademark mesenchymal stem cell (MSC) signature and profiled for embryonic pluripotency markers namely alkaline phosphatase, Oct4, Sox2, Nanog, SSEA3 and 4, and Klf4 by RT-PCR and nuclear localization of Oct4 and Nanog by immunocytochemistry. The amnion, although avascular, contains pro-angiogenic factors such as type I, III, IV and V collagen, laminin, and fibronectin in the extra cellular matrix. We, therefore, hypothesized that AMMSCs is pro-angiogenic. Thus, we demonstrate that MSCs derived from the amnion have a natural ability to initiate endothelialization and angiogenesis in vitro. Our results using a wound scratch assay and angiogenesis on Matrigel suggest a pro-angiogenic property of AMMSCs. We also show that native, uninduced AMMSCs are able to form endothelial rings in Matrigel. Further evidence was provided by RT-PCR showing the expression of pro-angiogenic factors such as Tie2, Ang1, VEGF, VEGFR, vWF, KDR and Flt4 in native AMMSCs. Taken together, our results suggest that MSCs from an avascular amnion have an inherent propensity for promoting angiogenesis and could be an ideal choice in wound healing, stroke and ischemic diseases that require rapid vascularization and tissue restoration. © 2012 Elsevier Ltd. All rights reserved.